EPIDEMIOLOGIA DA HANSENÍASE NO ESTADO DO PIAUÍ NO PERÍODO DE 2006 A 2013 - de Brito Melo Escórcio, Mirna Karine; Cerqueira de Sousa, Alessandra Maria; de Melo Rodrigues, Leonardo; Tolstenko Nogueira, Luciana (SANARE - Revista de Políticas Públicas, 2015)
-